A Comprehensive Analysis of the Journey, Factors, and Challenges of HIV/AIDS from a Global Perspective: A Literature Review - Marcela, Zevy; Ardian, Laurentius Johan (Journal of Diverse Medical Research: Medicosphere, 2025)
Abstract Background. HIV/AIDS remains one of the most significant global health challenges, particularly in developing regions such as Africa and Southeast Asia. Despite significant advances in treatment and prevention, the epidemic continues to be fueled by complex interactions between mental health, socio-economic, cultural, and behavioral factors. Objective: The objective of this study is to explore and analyze the various factors that contribute to the ongoing spread of HIV/AIDS, with a specific focus on the role of mental health, socio-economic status, and cultural practices. Method. This study employed a comprehensive literature review approach, analyzing data from peer-reviewed journals, WHO reports, and national health statistics. The review included articles published between 2019 and 2024, sourced from databases such as PubMed and Google Scholar, with a focus on studies that address the intersection of mental health and HIV, as well as the socio- cultural dynamics influencing the epidemic. Discussion. The results indicate that poor mental health significantly elevates the risk of engaging in high- risk behaviors associated with HIV transmission. Additionally, socio- economic disparities and cultural practices, such as stigma and discrimination, continue to exacerbate the prevalence of HIV, particularly in vulnerable populations. Conclusion: The findings underscore the critical need for integrating mental health services into HIV prevention and treatment programs. Furthermore, addressing the socio-cultural determinants of health is essential for reducing the global burden of HIV/AIDS and achieving more effective control of the epidemic.